El derecho justo en la Constitución colombiana de 1991 - Tovar, Luis Freddyur (2023)
This work demonstrates the 1991 ́s colombian Constitution consecrates a new concept of Law, according to the contemporary discussion. The author gets in to the bottom of colombian reality and concludes that the new Law concept, if it really exists, requires new approaches to their study and practice, task that claims to law schools a new way to prepare law operatives.